Penerapan Model Pembelajaran Learning Cycle 5E Untuk Meningkatkan Sikap Ilmiah Dan Hasil Belajar Biologi Siswa Kelas XI IPA 4 SMA Negeri 5 Pekanbaru - Irda Sayuti; Rosmaini S; Sri Andayannhi (Jurnal Pendidikan, 2012)
This study was aimed to improve the scientific attitudes andlearning outcomes of students in learning Biology by applying the “5ELearning Cycle”teaching modelinXIScience 4 class of SMAN 5 Pekanbaruin the academic year of 2011/2012. The study was conducted from Septemberto October2011. The subjects of the research were the students of XI Science4 class of SMAN 5 Pekanbaru, totaling 39 people. The parameters measuredwere the students’ scientific attitudes, students’ learning outcomes, students’and teacher’sactivities. In the first cycle the average of students’ scientificattitudeswas69.73% (Fair), and it wasincreasedin the second cycle up to84.75% (Good). Moreover, the students’ capability in comprehending thematerials givenin the first cyclewas76.95 (Less), and it was increased upto82.90in the second cycle (Enough).On the other side, the students’mastery,seeing from their post-testin the first cyclewas64.11% (Mastering)and35.89% (Not Mastering), and it was increasedin the second cycletobe84.61%(Mastering) and15.39% (Not Mastering). The activitiesof1studentsin the first cyclewas63.01% (Fair), and it wasincreasedin the secondcycleup to81.94% (Good). All of the teachers’ activitiesin the firstcyclewiththeaverage of 91.67% (Good) increasedin the second cycletobe100% (Excellent). Therefore, it can be concluded from this research thatthe application of5ELearning Cycleteaching model was successfullyimprovedthe scientific attitudes and learning out comes of studentsin learningBiology at XIScience 4 of SMAN 5Pekanbaruin the academic yearof2011/2012.